O registro reflexivo como instrumento na qualificação da prática pedagógica de professoras da educação infantil - Ruiz, Daniela (2022)
The object of this research is the reflective record as an instrument in the qualification of Pedagogical Practice of Early Childhood Teachers. The questions that guide this study are: Do Teachers of Infants and Very Young Children Record Activities of Their Day-to-Day Teaching? If Registered, Are Their Practices Supported by Reflection on Their Actions? How Does the Reflective Record Contribute to Teachers so That They Can Re-signify Their Pedagogical Practices? Is the Child's Listening Present in the Records? Is There a Reflection on This Listening? Our general objective is to verify how and if the reflective record qualifies the pedagogical practice of two teachers from a Basic Education Municipal School that serves children from 0 to 3 years old, located in the municipality of São Bernardo do Campo. The specific objectives are: To verify that the teachers of infants and young children record the pedagogical activities on a daily basis and, if they do, verify if their practices are supported by reflection on their actions; check if the reflective record contributes to the teachers so that they can re-signify their pedagogical practices; identify if the child's listening is present in the records and if there is a reflection on this listening. Our hypothesis is that the qualification of the reflective record through the teacher’s formation process, based on action-reflection-action, can bring about changes in the pedagogical practice, making it more humanized. The methodology used is qualitative in nature and the data collection’s instruments are the records made by two educators from the day care center and semi-structured interviews with the same teachers. We use as reference theoretical authors of Critical Pedagogy. Data analyzes were inspired by the analysis of content by Laurence Bardin. We list at first three categories: initial records, intermediate registers and reflective registers. The data indicate that the teachers of early childhood education record their practices, however, reflection becomes part of them as in which there is a reflective formative process. Reflections appear more clearly in the records and the planned pedagogical practices supported by the reflections carried out, demonstrate an increasingly close dialogue between reflection and action. It was possible to check that children's listening is also present in the records and that the teacher starts to account when looking at their practice becomes more critical, making it more humanized and based on a dialogic relationship with infants and young children. The teacher qualifies his practice from the moment he reflects on it, becoming authorial.